IMPROVING STUDENTS’ LISTENING SKILL USING PODCASTS - Syahabuddin, Khairiah; Rizqa, Khaira (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2021)
The purpose of this study is to discover the use of podcasts in improving students’ listening skills. The quantitative technique was used in this research: the data obtained from the pre-experimental technique. This research was conducted to find out the information about the improvement of students listening skills on using podcasts. This study involved 15 students in the fourth semester in the Department of English Language Education of Universitas Islam Negeri Ar-Raniry Banda Aceh. The sample was chosen by using purposive sampling who are qualified the certain criteria; sixth semester-students in Department of English Language Education of Universitas Islam Negeri Ar-Raniry Banda Aceh, and The students who have passed Basic Listening subject, Intermediate Listening subject, and Advanced Listening subject. However, the students faced difficulties in comprehending audio at the first meeting, after giving a treatment by using podcasts, the finding revealed that podcasts help students to improve their listening skills. It was proven by the improvement of the mean score of students’ pre-test and post-test (36.3 to 63.3). Overall, this study suggests that developing English listening skills can be boosted with Podcasts